Evaluation of temporal consistency of snow depth drivers of a Rocky Mountain watershed in southern Alberta. Issue 25 (20th October 2020) - Cartwright, Kelsey; Hopkinson, Chris; Kienzle, Stefan; Rood, Stewart B.
Abstract: Collecting spatially representative data over large areas is a challenge within snow monitoring frameworks. Identifying consistent trends in snow accumulation properties enables increased sampling efficiency by minimizing field collection time and/or remote sensing costs. Seasonal snowpack depth estimations during mid‐winter and melt onset conditions were derived from airborne Lidar over the West Castle Watershed in the southern Canadian Rockies on three dates. Each dataset was divided into five sets of snow depth driver classes: elevation, aspect, topographic position index, canopy cover and slope. Datasets were quality controlled by eliminating snow depth values above the 99th percentile value, which had a negligible effect on average snow depths. Consistent trends were observed among driver classes with peak snow accumulation occurring within the treeline ecotone, north‐facing aspects, open canopies, topographic depressions and areas with low slope angle. Although mid‐winter class trends for each driver were similar and watershed‐scale snow depth distributions were significantly correlated (0.76, p  < .01), depth distributions within the same driver class of the three datasets were not correlated due to recent snowfall events, redistribution and settling processes. Trends in driver classes during late season melt onset were similar to mid‐winter conditions but watershed scale distribution correlation results varied with seasonality (0.68 mid‐winter 2014 and melt onset 2016; 0.65 mid‐winter 2017 and melt onset 2016, p  < .1). This is due to the differing stages of accumulation or ablation and the upward migration in the 0°C isotherm during spring, when snow depth can be declining in valley bottoms while still increasing at higher elevations. The observed consistency in depth driver controls can be used to guide future integrated snow monitoring frameworks. Abstract : Seasonal snowpack depth estimations during mid‐winter and melt onset conditions were derived from airborne Lidar in the southern Canadian Rockies over 3 years. Each dataset was divided into five set of snow depth driver classes: elevation, aspect, topographic position index, canopy cover and slope. Consistent trends were observed among driver classes with peak snow accumulation occurring within the treeline ecotone, north‐facing aspects, open canopies, topographic depressions and areas with low slope angle. Lidar snow depth model quality control methods were also explored.